2017
DOI: 10.1016/j.arth.2017.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Patient Perceptions Regarding Outpatient Hip and Knee Arthroplasties

Abstract: These observations suggest that there is need for patient education regarding outpatient TJA. As outpatient procedures become more common, it is essential that patients understand the ambulatory surgery process, the benefits and risks of same day discharge, and their role in a successful outpatient experience.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(28 citation statements)
references
References 18 publications
2
24
0
2
Order By: Relevance
“…27,32 Another recent study revealed patients prefer to recover at home, even when they expect a need for more hospital days. 33 It comes as no surprise that patients undergoing same day discharge have reported excellent patient satisfaction when participating in a comprehensive OP total joint program that utilizes careful patient selection, refined surgical techniques, modern anesthesia protocols (including selective nerve blocks), and multimodal pain management regimens that limit the reliance on narcotic medications. 12,[34][35][36][37] The literature is largely in agreement supporting that OP TKA can be safely performed.…”
Section: Outcomes Of Outpatient Tkamentioning
confidence: 99%
“…27,32 Another recent study revealed patients prefer to recover at home, even when they expect a need for more hospital days. 33 It comes as no surprise that patients undergoing same day discharge have reported excellent patient satisfaction when participating in a comprehensive OP total joint program that utilizes careful patient selection, refined surgical techniques, modern anesthesia protocols (including selective nerve blocks), and multimodal pain management regimens that limit the reliance on narcotic medications. 12,[34][35][36][37] The literature is largely in agreement supporting that OP TKA can be safely performed.…”
Section: Outcomes Of Outpatient Tkamentioning
confidence: 99%
“…A study by Meneghini and Ziemba-David looked at patient perceptions of outpatient arthroplasty and found that of the 110 patients surveyed, only 3 expected to be discharged on the same day and over 50 percent expected to stay two or more nights in hospital. 26 However, more than 50 percent of men and 30 percent of women reported being comfortable with outpatient surgery. 26 This large discrepancy signals a need for adequate patient education prior to surgery to make sure that patients are aware of the option for outpatient arthroplasty when it is available.…”
Section: Patient Factorsmentioning
confidence: 99%
“…26 However, more than 50 percent of men and 30 percent of women reported being comfortable with outpatient surgery. 26 This large discrepancy signals a need for adequate patient education prior to surgery to make sure that patients are aware of the option for outpatient arthroplasty when it is available. A study by Churchill et al at our institution interviewed patients discharged as outpatients after THA and reported unrealistic expectations from the patients for speed of recovery as well as what to expect for post-operative pain.…”
Section: Patient Factorsmentioning
confidence: 99%
“…Over the past decade, there has been increasing interest in performing primary hip and knee replacement in the outpatient setting [1], [2], [3], [4], [5], [6], [7], [8], [9], [10], [11], [12], [13], [14], [15], [16], [17], [18], [19], [20], and rapid recovery protocols have created a natural evolution from the inpatient to outpatient setting [2], [3], [6], [10], [21], [22], [23]. The interest in outpatient arthroplasty also has been fueled by financial considerations including the ability to control costs within the episode of care, the potential for surgeon ownership in ambulatory surgery centers, and the ability of a surgeon to control his or her operating room and surgical care environment more easily in an ambulatory surgery center [1], [5], [8], [24].…”
Section: Forewordmentioning
confidence: 99%